2019
DOI: 10.1111/1346-8138.14820
|View full text |Cite
|
Sign up to set email alerts
|

Clonal change of methicillin‐resistant Staphylococcus aureus isolated from patients with impetigo in Kagawa, Japan

Abstract: Recently, the USA300 clone, which is a Panton–Valentine leukocidin (PVL)‐positive clonal complex 8‐staphylococcal cassette chromosome mec type IV (CC8‐IV) community‐acquired methicillin‐resistant Staphylococcus aureus (CA‐MRSA) strain, emerged in community and hospital settings in Japan. Hence, clonal types of CA‐MRSA strains are predicted to be changing. Nonetheless, long‐term surveillance of CA‐MRSA has not been conducted in Japan. Here, we investigated the transition and current status of CA‐MRSA strains is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Recently, SCC mec type IV has been increasing in the hospital‐acquired MRSA infections . In addition, both SCC mec types II and IV were frequently found in the same clonal complex in the previous study . Hence, in further nationwide surveillance, MLST is needed.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Recently, SCC mec type IV has been increasing in the hospital‐acquired MRSA infections . In addition, both SCC mec types II and IV were frequently found in the same clonal complex in the previous study . Hence, in further nationwide surveillance, MLST is needed.…”
Section: Discussionmentioning
confidence: 87%
“…A recent multicenter study on MRSA isolated from outpatients with impetigo in Kagawa reported that the most frequent SCCmec type was V. 5 The previous study in Tama also reported that the percentage of SCCmec type V in hospitals and clinics were 20.0% and 46.3%, respectively. 3 SCCmec type V was determined as non-typeable in our method, 9 but there was no non-typeable strain in this study.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations